cDNA cloning, biochemical and phylogenetic characterization of β- and β' -subunits of Candida albicans protein kinase CK2 - Zelada, Alicia Mercedes (2003)
We have previously reported that Candida albicans protein kinase CK2 is composed of two distinct catalytic (α- and α′-) and two distinct regulatory (β- and β′-) subunits. We report here the isolation of two cDNAs clones, CaCKB1 and CaCKB2, encoding C. albicans β- and β′-subunits, respectively. The predicted β- and β′- proteins have calculated molecular masses of 34 kDa and 31 kDa and show all major features conserved in β-subunits of other organisms, including the N-terminal autophosphorylation site, the internal acidic region and a potential metal-binding motif. The deduced amino acid sequence of C. albicans β-subunit displays 48% identity with that of Saccharomyces cerevisiae and has an unusually long C-terminal acidic region containing a putative autophosphorylation site. C. albicans β′ shows 54% sequence identity with its S. cerevisiae homologue. Semi-quantitative RT-PCR analyses indicate that the mRNAs corresponding to both subunits are present in similar amounts in the yeast and hyphal forms of the fungus. To evaluate the biochemical properties of C. albicans β- and β′-subunits, both proteins were expressed in Escherichia coli and purified. Experiments performed in vitro indicate that both recombinant subunits reconstitute a fully functional holoenzyme when incubated with stoichiometric amounts of human recombinant α-subunit, as judged by their ability to abolish basal phosphorylation of calmodulin by human recombinant α-subunit and the reversion of the inhibitory effect by polylysine. In addition, both regulatory subunits can be phosphorylated by human recombinant α subunit. Phylogenetic analysis of β- and β′-proteins of C. albicans and other organisms shows that the CKB gene duplication occurred before the split of the ascomycete and basidiomycete lineages. cDNA sequences of C. albicans CKB1 (Accession No. AF0599060) and CKB2 (Accession No. AY172319) have been deposited in the GenBank database.